Analogy Method Development for Cost Estimation of Software Design - Sarno, Riyanarto; Buliali, Joko Lianto; Maimunah, Siti (Makara Journal of Technology, 2002)
The important aspect of planning and managing software development project is to estimate the cost of a project. There are several methods for estimating the cost of a software development project, and the Analogy method is a method which gives relatively better estimates. This paper shows that the modified Analogy method selects a closer project reference, estimates more accurate project effort and cost. This study enhances the cost estimate technique by including valid and complete cost parameters, therefore the estimate of a project cost is better than the result of the standard Analogy method.